Flexible temperature sensors: A review - Arman Kuzubasoglu, Burcu; Kursun Bahadir, Senem (Sensors and actuators. A. Physical., 2020)
[Display omitted] The research and development of wearable sensors have gained a growing interest due to the advantage of being flexible, thin, and light, which makes them highly desirable for robotic and healthcare applications. One of the essential devices in wearable technology is flexible temperature sensors for body temperature detection. Recent advances in flexible temperature sensors based on nanomaterials and conductive polymers are evaluated in this review. The temperature-responsive mechanisms, temperature-sensitive materials, and production methods of temperature sensors and recent outcomes of related papers are explained and classified in a detailed perspective. The flexible temperature sensors based on nanomaterial-filled polymer composites, printed/coated conductors, and textiles are explained in terms of structures and performances by giving examples from recent literature studies. The reliability and challenges of flexible temperature sensors are outlined from the point of view of structural design and implementation.